Poverty measurement and theories of beneficence - S. Subramanian (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This note points to certain similarities of orientation and outcome between Derek Parfit's quest for a theory of beneficence and Amartya Sen's quest for a suitable realvalued representation of poverty. It suggests that both projects, in a certain sense, have been instructive failures. Using Sen's own work, the note also suggests a logically natural way of dealing with some of the problems in poverty measurement reviewed in it—but only to reject this way out on other compelling grounds. – quantity ; quality ; inequality ; identification ; aggregation
Keywords: I32; 330; Armut; Messung; Theorie